Nutritional, sensory, and quality attributes of heritage bred chicken and commercial broiler meat - Christiansen, Alexandra R. (Kansas State University, 2013)
Animal production factors can affect nutritional composition and quality of poultry meat. Quality attributes and fatty acid composition were evaluated on breast and thigh meat with skin from free range, heritage bred chickens (>116 day of age) (HB) and commercial broilers (<50 day of age) (CM). In addition, sensory and textural attributes were evaluated on breast and thigh meat of HB, and air or water chilled CM. Moisture and fat content was similar (P>0.05) between chicken types without skin. Thigh meat had at least 2.41% more fat (P<0.05) than breast meat; however, breast meat had at least 2.33% more moisture (P<0.05) regardless of skin inclusion or chicken type. Heritage meat with or without skin had a greater amount (P<0.05) of ω3 polyunsaturated fatty acids (PUFA) than CM regardless of chilling type and HB had a lower, more desirable ω6:ω3 ratio of 12.79 when compared to air or water chilled CM at 15.20 and 14.77, respectively. Heritage breast and thigh meat with skin contained 35.60 and 35.21% PUFA which was greater than (P<0.05) CM breast and thigh meat with skin at 20.96 and 20.45%, respectively. Whole carcass weight of CM, breast weight, and bone-in thigh weight was 71.30%, 148.0%, and 52.2% heavier (P<0.05), respectively, than HB weight. However, bone-in thigh yield was 2.1% higher (P<0.05) in HB. Commercial broiler breast and thigh meat was more tender (P<0.05) with higher myofibrillar tenderness and overall tenderness values and having less connective tissue than HB breast and thigh meat. Thigh meat from HB also had the highest (P<0.05) peak force values for Warner-Bratzler (3.47 kgf) and Allo-Kramer (7.22 kgf/g sample) shear tests. Thigh meat was perceived to be more juicy (P<0.05) and have more chicken flavor intensity (P<0.05) than breast meat. Heritage meat showed advantages in fatty acid profiles while CM meat showed advantages in yields and tenderness attributes.
Keywords: Environment; Production systems; Meat quality; Sensory; Poultry; Nutrition; Agriculture, General (0473); Animal Sciences (0475); Food Science (0359)